2018
DOI: 10.1155/2018/8308671
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Microbiota Transplantation Can Alleviate Gastrointestinal Transit in Rats with High-Fat Diet-Induced Obesity via Regulation of Serotonin Biosynthesis

Abstract: Aim We tested the hypothesis that fecal microbiota transplantation (FMT) could regulate the biotransformation of bile acids, such as deoxycholic acid (DCA) and cholic acid (CA), which in turn regulate the biosynthesis of serotonin in the gut and relieve gastrointestinal dysmotility in high-fat diet- (HFD-) induced obesity in rats. Methods Male Sprague-Dawley rats were randomly divided into the control diet group, HFD group, and HFD-fed with receiving FMT. HFD was fed for 12 weeks. At the end of two-week HFD, F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 43 publications
(53 reference statements)
1
20
0
Order By: Relevance
“…A downward trend was observed in serotonin levels post-FMT in the AN patient’s stool samples (Figure 6B). Similar FMT effects were described in rat intestines on a high-fat diet [46]. Additionally, the decreased expression of tryptophan hydroxylase 1, known as the rate-limiting enzyme in serotonin synthesis, was observed.…”
Section: Discussionsupporting
confidence: 76%
“…A downward trend was observed in serotonin levels post-FMT in the AN patient’s stool samples (Figure 6B). Similar FMT effects were described in rat intestines on a high-fat diet [46]. Additionally, the decreased expression of tryptophan hydroxylase 1, known as the rate-limiting enzyme in serotonin synthesis, was observed.…”
Section: Discussionsupporting
confidence: 76%
“…A 36-year-old male patient diagnosed with severe psoriasis for 10 years and IBS for 15 years was subjected to FMT twice via both upper endoscopy and colonoscopy with a 5-week interval. After the second FMT treatment for 5 weeks, the two conditions improved greatly ( Lai et al, 2018 ; Mullish et al, 2018 ; Sun et al, 2018 ; Krajicek et al, 2019 ; Yin et al, 2019 ). Although FMT is potentially effective in many microbiota-related disorders, helping establish trans-kingdom equilibrium between gut fungi, viruses and bacteria to promote the restoration of microbial homeostasis ( McSweeney et al, 2020 ), the effect of FMT depends on several factors, including the bacterial load and microbial composition and function of the recipient and the donor, the physiological and genetic factors related to the recipient and the donor, and FMT preparation and route of administration ( Fischer et al, 2016 ; Vermeire et al, 2016 ; Duvallet et al, 2017 ; Ianiro et al, 2017 ; Allegretti et al, 2019 , 2020 ; Ding et al, 2019 ; Paramsothy et al, 2019 ; Ramai et al, 2019 ; Wilson et al, 2019 ; de Groot et al, 2020 ; McSweeney et al, 2020 ).…”
Section: Modulation Of the Gut Microbiota For Prevention And Treatmenmentioning
confidence: 99%
“…This therapy can be an effective approach to obesity treatment [12,13]. Even though FMT has some limitations, several studies have tested its effectiveness and have demonstrated an improvement of some comorbidities associated not only with obesity [14] but also with other noncommunicable diseases [1518].…”
Section: Introductionmentioning
confidence: 99%